2021
DOI: 10.1007/s00726-021-03072-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of collagen peptide supplementation on body composition, collagen synthesis, and recovery from joint injury and exercise: a systematic review

Abstract: Collagen peptide supplementation (COL), in conjunction with exercise, may be beneficial for the management of degenerative bone and joint disorders. This is likely due to stimulatory effects of COL and exercise on the extracellular matrix of connective tissues, improving structure and load-bearing capabilities. This systematic review aims to evaluate the current literature available on the combined impact of COL and exercise. Following Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 51 publications
2
33
0
1
Order By: Relevance
“…Due to their moisture absorption properties, collagen and its fractions have demonstrated a significant role as valuable nutritive fibres and protein sources in human diets [ 2 ]. Collagen supplements may help with the treatment of degenerative bone and joint diseases, increase lean muscle gain, shorten recovery time, fix damaged joint structure, and improve cardiovascular performance [ 51 ]. Collagen promotes natural creatine, a key amino acid in post-workout muscle growth.…”
Section: Resultsmentioning
confidence: 99%
“…Due to their moisture absorption properties, collagen and its fractions have demonstrated a significant role as valuable nutritive fibres and protein sources in human diets [ 2 ]. Collagen supplements may help with the treatment of degenerative bone and joint diseases, increase lean muscle gain, shorten recovery time, fix damaged joint structure, and improve cardiovascular performance [ 51 ]. Collagen promotes natural creatine, a key amino acid in post-workout muscle growth.…”
Section: Resultsmentioning
confidence: 99%
“…In this sense, research has shown that supplementation with hydrolyzed collagen (≈10 g per day) can increase cartilage thickness in patients with osteoarthritis [ 112 ] and decrease knee pain in athletes [ 113 ]. Indeed, the recent systematic review performed by Kahtri et al (2021) [ 47 ] concluded that ‘collagen peptides and specific gelatin products have strong evidence in improving joint pain and functionality (especially at doses of 15 g/day)’. The data presented suggest a benefit of gelatin along with vitamin C and/or hydrolyzed collagen supplements; therefore, it is expected that future clinical studies need to confirm this recommendation in injury-related specific conditions [ 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…Сделан вывод о том, что экзогенный коллаген можно использовать в качестве безопасной терапевтической добавки для контроля симптомов боли на фоне ОА и остеопороза [36]. Опубликованы положительные результаты исследования, включающие специальные комплексы физических упражнений в сочетании с приемом коллагена [38]. Основанием для инициации этого исследования послужила гипотеза о «механической трансдукции», которая предполагает, что механическая нагрузка на ткани сухожилий во время упражнений создает сигнальный каскад в клетках этих тканей, увеличивает выработку белков матрикса и последующую гипертрофию сухожилий, что в сочетании с экзогенным коллагеном создает дополнительные преимущества [39].…”
Section: обоснование применения экзогенного коллагена при остеоартритеunclassified